2020
DOI: 10.1021/acsami.0c05978
|View full text |Cite
|
Sign up to set email alerts
|

Burn-In Degradation Mechanism Identified for Small Molecular Acceptor-Based High-Efficiency Nonfullerene Organic Solar Cells

Abstract: Organic solar cells (OSCs) have again become a hot research topic in recent years. The record power conversion efficiency (PCE) of OSCs has boosted to over 17% in 2020. Apart from the high PCE, the stability of OSCs is also critical for their future applications and commercialization. Recently, many studies have proposed that burn-in degradation can be considered as an ineluctable barrier to long-term stable OSCs. However, there is still lack of studies to explain the detailed mechanism of this burn-in process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 70 publications
1
42
0
Order By: Relevance
“…As shown in Figure 3, the IDIC16‐based PSC shows poor thermal stability and dramatically decreased PCE even after 1 h under a continuous thermal storage of 85 °C. Moreover, it only retained ≈50 % of its initial PCE when stored at 85 °C for only 18 h. On the contrary, the PF1‐TS4‐based all‐PSC presents outstanding thermal stability and still retained ≈70 % of its initial PCE after being stored at 85 °C for 180 h. It was noticed that the all‐PSC exhibits a major drop in PCE during the first 30 hours annealing, which is due to the so called burn‐in degradation caused by the instability of interfaces and electrodes [42] . Furthermore, the IDIC16‐based PSC shows a much larger drop in PCE than the PF1‐TS4‐based all‐PSC, which may be attributed to the combination of burn‐in degradation and poor morphological stability of its active layer (discussed right below).…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 3, the IDIC16‐based PSC shows poor thermal stability and dramatically decreased PCE even after 1 h under a continuous thermal storage of 85 °C. Moreover, it only retained ≈50 % of its initial PCE when stored at 85 °C for only 18 h. On the contrary, the PF1‐TS4‐based all‐PSC presents outstanding thermal stability and still retained ≈70 % of its initial PCE after being stored at 85 °C for 180 h. It was noticed that the all‐PSC exhibits a major drop in PCE during the first 30 hours annealing, which is due to the so called burn‐in degradation caused by the instability of interfaces and electrodes [42] . Furthermore, the IDIC16‐based PSC shows a much larger drop in PCE than the PF1‐TS4‐based all‐PSC, which may be attributed to the combination of burn‐in degradation and poor morphological stability of its active layer (discussed right below).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it only retained % 50 % of its initial PCE when stored at 85 8C for only 18 h. On the contrary, the PF1-TS4-based all-PSC presents outstanding thermal stability and still retained % 70 % of its initial PCE after being stored at 85 8C for 180 h. It was noticed that the all-PSC exhibits a major drop in PCE during the first 30 hours annealing, which is due to the so called burn-in degradation caused by the instability of interfaces and electrodes. [42] Furthermore, the IDIC16-based PSC shows a much larger drop in PCE than the PF1-TS4-based all-PSC, which may be attributed to the combination of burn-in degradation and poor morphological stability of its active layer (discussed right below). To understand the thermal stability difference between these two devices, atomic force microscopy (AFM) and transmission electron microscopy (TEM) measurements were performed to study their active layer morphologies (Figure 4).…”
mentioning
confidence: 98%
“…Our previous study has reported the burn‐in degradation of the control device, where the unencapsulated device showed around 50% of PCE loss after the burn‐in test for 5 h, as also shown in Figure 8a. [ 20 ] In this study, the unencapsulated two TiO x ALD cycles modified device showed improved device stability compared with the control device. It was found that the J sc and FF of the device decreased by around 10% and 20%, respectively, which contributed to the 30% degradation in PCE.…”
Section: Resultsmentioning
confidence: 76%
“…[ 18,19 ] We have previously reported a 14% PCE for the N3‐based OSCs in an inverted device structure based on the ZnO layer. [ 20 ] The unencapsulated device showed around 50% of PCE loss after the burn‐in degradation test for 5 h, where the instability of the interface layers and the electrode was found to be the leading cause. Herein, modifying the ZnO layer can be a feasible method to bring further performance and stability improvement to this type of device.…”
Section: Introductionmentioning
confidence: 99%